Nested graft for chronic ulcer in scar tissue after heroin extravasation in a drug addict. Issue 1 (February 2021) - Monari, Paola; Venturuzzo, Anna; Moro, Ruggero; Calzavara-Pinton, Piergiacomo; Gualdi, Giulio
Abstract: Introduction: Nested graft is a surgical technique that allows to manage difficult-to-treat medical conditions such as chronic cutaneous ulcers, thanks to the high efficacy it has in reverting the fibroblasts senescence. Because of its peculiar regenerative property, nested graft is a surgical technique suitable also for the treatment of cutaneous ulcers developing on fibrotic scar tissue. Case report: We reported the case of a 45-year-old man, drug-addict, with a large ulcer on the back of the right forearm in the context of scar fibrotic tissue. This lesion resulted from a previous heroin extravasation treated with a dermo-epidermal skin graft, that was accidentally scratched away by mechanical trauma. After several therapeutic failures with topical medications, we decided to treat the ulcer performing a skin graft using the nested graft technique. No adverse events were reported by the patient during or after the surgery. At the clinical evaluation performed three years later the wound was completely healed. Conclusions: Nested graft represents a safe and easy-to-use technique that can be successfully used to treat ulcers on scar tissue, ensuring the achievement and the long-term maintenance of optimal resistance and aesthetic results. Highlights: The extravasation of drugs is a possible cause of skin ulcers. Treatment of skin ulcers on fibrotic tissue is challenging. Nested graft, by promoting tissue regeneration, allows the healing of skin ulcers on scar tissue.